First line modified Folfirinox versus gemcitabine for advanced pancreatic cancer: A single institution retrospective experience - Emrah Eraslan; Fatih Yildiz; Gulnihal Tufan; Ferit Aslan; Umut Demirci; Omur Berna Oksuzoglu (Journal of Oncological Sciences, 2019)
Background: Advanced pancreatic cancer (APC) is a highly lethal malignancy which has one of the worst treatment outcomes. Modified (m)FOLFIRINOX is an intense but a proven treatment approach with a survival benefit for APC. Although mFOLFIRINOX demonstrated survival benefit compared with gemcitabine monotherapy, the standard treatment in previous years, toxicity is a difficult aspect of this treatment. Methods: A retrospective analysis of patients referred to Medical Oncology Clinics of Ankara Oncology Research and Training Hospital with the diagnosis of inoperable locally advanced or metastatic pancreatic cancer and treated with mFOLFIRINOX or gemcitabine monotheraphy from March 2013 to April 2018 was performed. Results: Forty three patients and 37 patients were included in mFOLFIRINOX and gemcitabine groups, respectively. The mean age of the patients was 53.74 years (range: 32–69) and 65,7 years (range: 47–82) for mFOLFIRINOX and gemcitabine, respectively (95% CI, p < 0.001). All patients, except one, had ECOG performance status of 0 or 1 in mFOLFIRINOX group. In contrast, nine patients had ECOG performance status of 2 in the gemcitabine group (95% CI, p = 0.002). When the patients were evaluated for response, 11 (25.6%) and 6 (16.2%) had partial remission with mFOLFIRINOX and gemcitabine, respectively. Median PFS and OS was 5,73 (95% CI, 2,57-8,90) months and 8.77 (95% CI, 6.54–10.99) months with mFOLFIRINOX and 2,77 (95% CI, 2,29-3,24) months and 5.80 (95% CI, 3.08–7.92) months with gemcitabine, respectively. mFOLFIRINOX regimen was more toxic than gemcitabine regimen. The incidences of all-grade neutropenia, neuropathy, and emesis were more prominent in the mFOLFIRINOX group. Conclusion: mFOLFIRINOX is a difficult regimen for both patients and physicians with significant toxicity with a greater survival benefit. The survival benefit was modest in this real-life experience. Patient selection bias and small sample size of this retrospective study should be considered. Keywords: Pancreatic cancer, First-line therapy, mFOLFIRINOX, Gemcitabine